FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PETANI IKAN KOLAM DI DESA HAUR GADING - MUHAMMAD RIZKA MAULANA; KHAIRI PAHLEVI (PPJP Universitas Lambung Mangkurat, 2019)
Fisheries potential contained in Hulu Sungai Utara District into its own record in an attempt to boost a greater role in the economy Hulu Sungai Utara District. Besides this, the human recources to move the fishery sector has prospect for development. Because the fishery potential is very large and is supported by natural resources is great but the production of the fisheries sector is still relatively small so to the need for policies that can encourage to increase fish production in particular subsector of aquaculture in Hulu Sungai Utara and indirectly will improve people’s welfare especially fish farmers. This study aims to determains what factors are some influence on farmers’ income fish pond, method of this study is research that is descriftive quantitative research object income of farmers in HaurGading Village research object income of farmers in HaurGading Village using this type of primary data obtained from interviews of all fish farmers fish pond with a population of 32 respondents and secondary data obtained from the relevant agencies. The result showed that the factors of land, feed, seed and drugs affect concurrently or simultaneislyti the farmers income fish pond, and there are factors of land and seeds that are partially significant effect on the income of farmers fish pond in HaurGading District.Keyword: Fish, Pond, Economy